On simplification system of partial differential equations with variable - Jurgaitis, Donatas (Lietuvos matematikos rinkinys, 2002)
The system with junior variable coefficients of Moisil–Theodoresco is analysed in the article. The line of the system degenerates in points of the hyper-plane. A changeable element is found, with the help of which the structure of the selected coefficient is changed by the power line of the system coefficient exposing element. The structure of this coefficient conforms to the structure of the principal matrix of the system coefficient exposing element. A formal changeable element is found, which allows the system to be divided into partial systems, when the principal matrix of the exposing element of the system junior members is blocking.